Partnership Between Educational Institutions Ma'arif NU and Unicef In Building Inclusive Madrasah Program In Central Java - Ibda, Hamidulloh (Khatulistiwa, 2020)
This study aims to describe and analyze an inclusive madrasah program as a form of partnership between the Educational Institutions Ma’arif NU of Central Java and Unicef. This descriptive qualitative study was conducted in Banyumas, Brebes, Kebumen and Semarang Districts. Inclusive Madrasah are carried out not only in schools and madrasah, but also in universities, namely in IAINU Kebumen and UNU Purwokerto, Banyumas. There are obstacles and opportunities for developing inclusive madrasah. Of these obstacles, inclusive madrasah have a great opportunity because have the support of various institution, communities, and even universities.